Death star - 4 0 16; (Susan Kopman) McNab, David.;Holt, Sarah.;Lewis, Susan K.;Cox, Donna J.; 5 Dox Distribution (Firm);WGBH Video (Firm) ([Boston] : WGBH Boston Video, 2006)
For 30 years, scientists have been on the hunt for the source of the most powerful and mysterious explosions in the universe.
DVD.;Originally broadcast on the television series Nova in 2002.
Edited by David Fairhead ; camera, Kris Denton, Clive North ; animation, Red Post Production andrew Jadavji, Gareth Edwards ; art director and choreographer, Robert Patterson.
Narrated by Stacy Keach.
DVD, region 1; NTSC; Dolby Digital; letterboxed.
Closed-captioned.
Keywords: 2 -- 0; 6; Gamma ray bursts.;Educational television programs.;DVDs. -- 20; 20; Science television programs.;DVDs. -- 2